2018
DOI: 10.1111/rode.12378
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rural electrification on income and education: Evidence from Bhutan

Abstract: We investigate the impact of a rural electrification program on household income and children's schooling in rural Bhutan. Using propensity score matching, we find that electrification had a statistically significant impact on nonfarm income and education. Nonfarm income increased by 61 percent and children gained 0.72 additional years of schooling and 9 minutes of study time per day. We do not observe significant effects on farm income. Results are consistent and robust to different matching algorithms. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…This increase in study time varies on average between 94 and 137 minutes per day. Kumar and Rauniyar (2018) achieve similar results. These authors examine the impact of a rural electrification programme on household income and children's schooling.…”
Section: Introductionsupporting
confidence: 58%
“…This increase in study time varies on average between 94 and 137 minutes per day. Kumar and Rauniyar (2018) achieve similar results. These authors examine the impact of a rural electrification programme on household income and children's schooling.…”
Section: Introductionsupporting
confidence: 58%
“…One of them was Samad and Zhang (2017), which evaluated different levels of electricity availability in the context of RERED Programme in Bangladesh which also had a technical support and affordability component. Lee (2019), Kurata (2018), Kumar (2018), Koima (2019), Khandker (2014), Khandker (2013), Fuji (2018, Ding (2018), , Chen (2019), , Chakravorty (2014), Blimpo (2018), Bezerra (2017), Bernard (2014), Bensch (2015), Bensch (2012), Barron (2017), Arráiz (2015), Alcazar (2007), Akpandjar (2018), Akpandjar (2017), Aevarsdottir (2017), Adusah-Poku (2019).…”
Section: Figure 6: Distribution Of Included Studies By Intervention Typementioning
confidence: 99%
“…In addition, the evaluation of the survey demonstrated that no positive effects of electrification were achieved in the field of education, which was contrary to initial assumptions. However, the correlation between electrification and educational success can usually be observed as a long-term effect since it depends on the number of years of schooling and on the downstream effects into the labour market (Kumar et al 2018). Therefore, this sector should be the focus of future observations.…”
Section: Resultsmentioning
confidence: 99%